Object-oriented software engineering - Schach, Stephen R. (McGraw hill, 2008)
Object-Oriented Software Engineering is written for both the traditional one-semester and the newer two-semester software engineering curriculum. Part I covers the underlying software engineering theory, while Part II presents the more practical life cycle, workflow by workflow.